ASESMEN PERKEMBANGAN BAHASA ANAK USIA DINI DI RA AL-AZHAR LANGSA - Farazia Rezki Putri; Zainuddin Zainuddin (Universitas Negeri Medan, 2022)
This study aims to tell or describe observations on early childhood language development at RA Al-Azhar Langsa. To develop early childhood language, RA Al-Azhar langsa provides stimulation in the form of teaching materials with the principle of learning to play, meaning that the child's playing is the learning process. This research is a case study research with a qualitative descriptive approach conducted at RA Al-Azhar Langsa. The purpose of this study was to find out how the assessment of early childhood development at RA Al-Azhar Langsa. The data collection technique that the author uses is observation followed by interviews. The results obtained are that the assessment carried out at RA Al-Azhar Langsa is carried out every day, by documenting both in the form of photos of some of the activities carried out by the child and an assessment sheet which then reports on the child's development will be compiled and reported by the teacher to parents. The recommendation that the author can suggest is that teachers continue to be able to develop assessments and develop their own assessment instruments so that children's development seems to have clear progress.